Aspidistra yichunensis (Asparagaceae), a new species from Jiangxi, China - You, Yue; Gao, Yan; Wan, Xin-Yu; Lin, Chun-Rui (Phytotaxa, 2026)
Aspidistra yichunensis, a new species of Asparagaceae from Jiangxi Province, southeastern China, is described and illustrated. The new species is morphologically similar to Aspidistra sichuanensis, but differs by its suburceolate perianth, lobes suberect or slightly recurved, apex rounded and usually cucullate, inside with 2–4 longitudinal ridges and thickened at base, and smaller stigma irregularly 3-lobed, each lobe shallowly 2–3-lobed again, with involuted margins. Its pollen with granulate exine. This new species is only known from Yichun City in Jiangxi, China.